Rapid and Femtogram-level Sensitive Detection of Blastocystis spp. Using Colorimetric and Fluorometric LAMP Assays: Analytical and Clinical Validation - Roaa Zedan; Huseyin Tombuloglu; Ayman Elbadry (Journal of Applied Microbiology, 2026)
Abstract Background/aim Blastocystis spp. is a genetically diverse protozoan parasite, often underdiagnosed due to low sensitivity and technical issues of current diagnosis techniques, wet mount microscopy and PCR. To bridge this gap, we developed loop-mediated isothermal amplification (LAMP) platforms, namely colorimetric (cLAMP) and fluorometric (fLAMP) for rapid and sensitive detection of Blastocystis spp. Materials and methods A cohort of 197 stool samples from patients with gastrointestinal conditions were screened. The diagnostic performance, analytical sensitivity, and speed of the LAMP assays was benchmarked against a gold-standard quantitative PCR assay. Results Results showed that both LAMP assays provided ultra-rapid detection, achieving mean detection times of 24.2 minutes for fLAMP and 29.8 minutes for cLAMP (compared to 36.5 minutes for qPCR; p < 0.001). In analytical sensitivity evaluations using purified plasmid DNA controls, both assays achieved femtogram-level limits of detection (LoD) (5 fg μL−1). In clinical copro-DNA matrices, fLAMP and cLAMP demonstrated LoD of 1.43 pg μL−1 and 14.3 pg μL−1, respectively. In clinical cohort evaluations, fLAMP demonstrated superior diagnostic sensitivity (94.1%) and overall accuracy (92.3%), while cLAMP offered high diagnostic sensitivity (95.8%), specificity (85.0%), and accuracy (90.1%) with naked-eye visual interpretation. Conclusion This study introduces a dual-platform LAMP system offering femtogram-level sensitivity and rapid detection of Blastocystis spp. within 30 minutes following DNA extraction. While fLAMP provides high-precision diagnostic accuracy, cLAMP offers an accessible, visual screening tool well-suited for low-resource environments.